2021
DOI: 10.3390/fermentation7030130
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Se-Nanoparticles from Bacterial Biotransformation

Abstract: Selenium nanoparticles (SeNPs) are gaining importance in the food and medical fields due to their antibacterial properties. The microbial inhibition of these kinds of particles has been tested in a wide range of Gram (+) and Gram (−) pathogenic bacteria. When SeNPs are synthesized by biological methods, they are called biogenic SeNPs, which have a negative charge caused by their interaction between surface and capping layer (bioorganic material), producing their high stability. This review is focused on SeNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 144 publications
1
43
0
Order By: Relevance
“…johnsonii La1 in the supplemented medium was presented in the non-enriched medium (10 h and 12 h, respectively). It is known that some LAB activates metabolic processes in the presence of salts such as Na 2 SeO 3 due to the detoxification mechanism (Escobar-Ramírez et al, 2021). However, the cell concentration was higher in media without supplementation, which coincides with the results reported by Martínez et al (2020).…”
Section: Fermentation Kineticssupporting
confidence: 87%
See 1 more Smart Citation
“…johnsonii La1 in the supplemented medium was presented in the non-enriched medium (10 h and 12 h, respectively). It is known that some LAB activates metabolic processes in the presence of salts such as Na 2 SeO 3 due to the detoxification mechanism (Escobar-Ramírez et al, 2021). However, the cell concentration was higher in media without supplementation, which coincides with the results reported by Martínez et al (2020).…”
Section: Fermentation Kineticssupporting
confidence: 87%
“…In contrast, the accumulation of selenium in enriched media at a higher concentration of the MIC is related to the transformation of selenite to elemental selenium deposited near the cell membrane (Kousha et al, 2017). Escobar-Ramírez et al (2021) reported that selenium accumulated in the cell periphery is accumulated simultaneously in the periplasm, especially in those bacteria producing seleno nanoparticles. However, in different cases, the Se bioaccumulation has not affected the cellular growth, specifically in the stationary phase.…”
Section: Fermentation Kineticsmentioning
confidence: 99%
“…Which, two genes SelA and SelD are located in the probiotic strains genome and involved in Se metabolism 62 , 63 . So, the helpful effect of nanoparticles delivered to the gut microbiota, aiming to reduce the pathogens, by eliminated the growth of harmful microbes and improved beneficial bacteria as probiotics 64 , 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Several experiments on bacteria using transmission electron microscopes have shown that SeNPs permeate the cells, supporting this claim. , Furthermore, in the presence of oxygen and proton, SeNPs break down to ions, making infusion easier . When SeNPs enter the cell, they interact with biological components and structures such as proteins, deoxyribonucleic acid (DNA), and lipids . For example, SeNPs disrupt protein synthesis by binding with the ribosome and denaturing it, causing the translation process to cease .…”
Section: Resultsmentioning
confidence: 99%
“… 82 When SeNPs enter the cell, they interact with biological components and structures such as proteins, deoxyribonucleic acid (DNA), and lipids. 83 For example, SeNPs disrupt protein synthesis by binding with the ribosome and denaturing it, causing the translation process to cease. 84 SeNPs also interact with DNA molecules, which can result in DNA denaturation and shearing, as well as cell division disruption.…”
Section: Resultsmentioning
confidence: 99%